Pelatihan Keterampilan Pijat Refleksi dan Pembuatan Jamu Tradisional sebagai Upaya Pengembangan Ekonomi Masyarakat Marginal di Nagari Rao-Rao Kabupaten Tanah Datar - Novelni, Ringga; Mentari, Tyas Asih Surya; Dewi, Siska Miga; Oktarina, Rahmi; Sartika, Diza (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to improve the skills of marginalized community members in Nagari Rao-Rao in beauty services, particularly in reflexology massage and traditional herbal medicine production, to increase their income. The implementation method involved training activities through demonstrations, hands-on practice, and mentoring in reflexology massage and the preparation of traditional herbal drinks using plants commonly grown around their homes, such as ginger, turmeric, aromatic ginger (kencur), temulawak (Curcuma xanthorrhiza), and lemon. The evaluation instrument used questionnaires, and the data were analyzed descriptively. The results of the community service program showed that the marginalized community group in Nagari Rao-Rao: (1) mastered beauty service skills in the field of reflexology massage; (2) was able to produce traditional herbal products from plants available in their home gardens; and (3) developed motivation to start their own businesses as entrepreneurs to support community economic development.